Mechanical compliance enhances the impulsive energy absorption of glassy polymer films - Jonathan G. Raybin; Katherine M. Evans; Edwin P. Chan (Proceedings of the National Academy of Sciences, 2026)
From soft tissues to seismic damping systems, mechanical compliance is widely exploited by natural and engineered systems for dissipating energy and averting catastrophic failure. While this principle is well understood under quasi-static conditions, the role of compliance at extreme strain rates is less explored. Here, we integrate laser-ablation-based membrane expansion testing, ultra-high-speed imaging, and mechanical modeling to study the real-time dynamic response of glassy poly(methyl methacrylate) (PMMA) films subjected to impulsive loading at strain rates ranging from 10 6 s − 1 to 10 8 s − 1 . Although PMMA ordinarily exhibits low impact resistance, under these conditions, the films deform and can sustain unexpectedly large biaxial strains without catastrophic failure. By tuning the film thickness, we demonstrate that the increased compliance of thinner films promotes plastic deformation, enabling more effective energy absorption. Our findings suggest strategies for designing lighter, tougher materials for impact mitigation under extreme dynamic loading.